Suture Anchors Fixation in MPFL Reconstruction using a Bioactive Synthetic Ligament - Berruto, Massimo; Ferrua, Paolo; Tradati, Daniele; Uboldi, Francesco; Usellini, Eva; Marelli, Bruno Michele (Joints, 2017)
Medial patellofemoral ligament (MPFL) reconstruction has a key role in patellofemoral instability surgery. Many surgical techniques have been described so far using different types of grafts (autologous, heterologous, or synthetic) and fixation techniques. The hereby described technique for MPFL reconstruction relies on the use of a biosynthetic graft (LARS Arc Sur Tille, France). Fixation is obtained by means of suture anchors on the patellar side and a resorbable interference screw on the femoral side locating the insertion point according to Schottle et al. An early passive range of motion (ROM) recovery is fundamental to reduce the risk of postoperative stiffness; a partial weight bearing with crutches is allowed until 6 weeks after the surgery. In our experience, the use of a biosynthetic graft and suture anchors provides stable fixation, minimizing donor site morbidity and reducing the risk of patellar fracture associated with transosseous tunnels. This technique represents a reliable and reproducible alternative for MPFL reconstruction, thereby minimizing the risk of possible complications.
Keywords: medial patellofemoral ligament; suture anchors; biosynthetic ligament; patellofemoral instability